Phenotypic change in neutrophils in patients with Acne Vulgaris - A.Sh. Aliyev; M.V. Zalyalieva; U.A. Tashkenbaeva; Sh.R. Aliyev; F.Kh. Abboskhonova; S.A. Khudoyberdieva (Zien Journals, 2021)
The widespread prevalence, material and moral damage, a tendency to chronicity and frequent recurrence, lack of effectiveness of therapy determine the relevance of the studied problem
Keywords: acne vulgaris; neutrophilic granulocytes; phenotype; surface receptors